THE EFFECT OF EXPERIENCE QUALITY ON CUSTOMER PERCEIVED VALUE AND CUSTOMER SATISFACTION AND ITS IMPACT ON COFFEE TRUCK CUSTOMER LOYALTY IN LHOKSEUMAWE CITY - Muhammad Aris Muladi; Jullimursyida; Ikramuddin; Naufal Bachri; Mariyudi; Sapna Biby (CV. Radja Publika, 2025)
The purpose of this study is to examine the influence of Experience Quality on Customer Perceived Value and Customer Satisfaction, and its impact on Customer Loyalty in Lhokseumawe City. The data in this study were 135 Truck Cafe visitors who responded to a questionnaire distributed through Google Forms. The data analysis tool used Structural Equation Modeling, operated with Amos. The results showed that Experience Quality had a significant effect on Customer Perceived Value, Customer Satisfaction, and Customer Loyalty. Then Customer Perceived Value has a significant effect on Customer Satisfaction and Customer Loyalty. Furthermore, the direct test also found that Customer Satisfaction had an effect on Customer Loyalty. And in the mediation effect test, it was found that Customer Perceived Value and Customer Satisfaction were partial mediating variables between Experience Quality and Customer Loyalty of truck cafes in Lhokseumawe City, and full mediation between Customer Perceived Value and Customer Loyalty. The results of this study are expected to provide an important contribution for stakeholders in developing coffee shop business management strategies, especially for truck coffee .